2009
DOI: 10.1093/esr/jcn080
|View full text |Cite
|
Sign up to set email alerts
|

Life Outcomes of Childless Men and Fathers

Abstract: Using data from the first wave of the Netherlands Kinship Panel Study (NKPS) for 1,451 men aged 40-59 we examine the impact of permanent childlessness. We extend on previous work by focusing on partnership history as a possible explanation for differences between childless men and fathers. Our results show that the impact of childlessness is weaker than we had expected. Many initial differences between childless men and fathers are attributable to differences in their partnership history. Nevertheless, childle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 68 publications
3
71
0
3
Order By: Relevance
“…For men, for example, firstborn sons (but not daughters) were associated with relatively more happiness (although subsequent children had no effect; Kohler, Behrman, & Skytthe, 2005). More recent research is consistent with these findings for men, suggesting that fathers with children in the home report higher life satisfaction than childless men and nonresident fathers (Keizer et al, 2010). A recent study also revealed parenthood to be more consistently linked to well-being among men than women: Fathers reported experiencing greater life satisfaction, happiness, positive affect, and meaning and less depression than did childless men, but mothers only reported less depression (Nelson et al, 2013).…”
mentioning
confidence: 66%
“…For men, for example, firstborn sons (but not daughters) were associated with relatively more happiness (although subsequent children had no effect; Kohler, Behrman, & Skytthe, 2005). More recent research is consistent with these findings for men, suggesting that fathers with children in the home report higher life satisfaction than childless men and nonresident fathers (Keizer et al, 2010). A recent study also revealed parenthood to be more consistently linked to well-being among men than women: Fathers reported experiencing greater life satisfaction, happiness, positive affect, and meaning and less depression than did childless men, but mothers only reported less depression (Nelson et al, 2013).…”
mentioning
confidence: 66%
“…De literatuur toont dat het krijgen van kinderen mannen 'transformeert ' (Eggebeen & Knoester, 2001). Het krijgen van kinderen betekent het krijgen van verantwoordelijkheden en verplichtingen: als vader behoor je je op een juiste manier te gedragen en het goede voorbeeld te geven aan je kinderen Eggebeen & Knoester, 2001;Keizer, Dykstra & Poortman, 2009;Kendig et al, 2007;Knoester & Eggebeen, 2006). Dit leidt er vaak toe dat het hebben van kinderen ouders ervan weerhoudt om zich te gedragen op manieren die schadelijk zijn voor hun gezondheid (Kendig et al, 2007).…”
Section: Mechanismenunclassified
“…More recently there have been investigations into how fatherhood affects men"s own well-being. The few studies addressing this issue indicated a better social integration and closer family ties of fathers (Eggebeen and Knoester 2001;Keizer, Dykstra, and Poortman 2010). Furthermore, it has been argued that a decreasing involvement of fathers in bringing up their children leads to an increased burden on women, who have to shoulder their stronger labour-market engagement without relief from their roles in the home (Jensen 1999).…”
Section: Introductionmentioning
confidence: 99%